THE IMPLEMENTATION OF BILINGUAL METHOD IN TEACHING CHEMISTRY TO THE SECOND YEAR STUDENTS OF RSBI CLASS AT SMA NEGERI 1 BOYOLALI IN 2010/ 2011 ACADEMIC YEAR - NATALIA, DEVIA ELVA (2011)
This qualitative research aims at describing the process of teaching- learning Chemistry at the second year students of RSBI class at SMA Negeri 1 Boyolali. It is conducted to describe the procedures of Chemistry teaching-learning process, problems are faced by the teacher, and students' responses to the implementation of bilingual method in teaching Chemistry. This descriptive research involves describing and interpreting events, condition, or situation of the present. The subjects of the study are the Chemistry teacher and the second year students of RSBI class at SMA Negeri 1 Boyolali. The methods of data collection are observation, interview, and document. The finding shows that the implementation of Bilingual Method in teaching Chemistry to the second year students of RSBI class at SMA Negeri 1 Boyolali in 2010/2011 academic year is not different from teaching Chemistry on the other class. The most significant difference is in the use of English in explaining the material. The teacher only uses 30% English and 70% Indonesian. Indonesian was dominant than English. The teacher applies interesting techniques such as experiment, discussion or work group, and presentation in her teaching-learning process. The materials in the textbook are written in Bilingual.